PERKEMBANGAN OBJEK WISATA TALAO PAUAH PARIAMAN SEBAGAI WISATA BAHARI TAHUN 2019-2024 - Popi Afrilora; Meri Erawati; Liza Husnita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the development of the Talao Pauh marine tourism attraction in Pariaman City during the 2019–2024 period, identify factors influencing its development, and assess its impact on the economy of the surrounding community. This study used a qualitative method with a descriptive approach. Data were collected through in-depth interviews with local government officials, tourism attraction managers, and the local community, supplemented by field observations and documentation studies. The results indicate that the Talao Pauh tourist attraction has experienced significant development, particularly in aspects of accessibility, the provision of supporting tourism facilities, and increasing the number of tourist visits. The main factors driving this development include government policy support, attractive natural resource potential, and active community participation in tourism activities. However, this study also found several obstacles, such as suboptimal integrated management, limited supporting infrastructure, and the emergence of environmental impacts due to tourism activities. From an economic perspective, the development of Talao Pauh has had a positive impact on increasing community income through tourism services, culinary businesses, and souvenir sales. Therefore, this study emphasizes the importance of synergy between the government, managers, and the community in realizing the